Apprehensions of nurse managers on evidence-based practice - Fernanda Carolina Camargo; Mayla Borges Goulart; Helena Hemiko Iwamoto; Maria Rizoneide Negreiros de Araújo; Divanice Contim (Universidade Federal do Rio de Janeiro, 2017)
Abstract Objective: To analyze the apprehensions of nurse managers in the implementation of the Evidence Based Practice in a Teaching Hospital of Triângulo Mineiro. Method: Qualitative research guided by the Theory of the Diffusion of Innovations. Five workshops were conducted per focal group (n = 18 participants), conducted by hermeneutic-dialectic interactions between August and September/2016. Textual records resulting from each workshop were analyzed by semantic categories. Results: Aspects conditioning to the implementation of the Evidence Based Practice permeate from elements related to the fragmentation of the care network to the necessary expansion of the governability of the nurse managers to put changes into practice in their sectors. Most importantly, timely access to the results of research conducted at the teaching hospital was mentioned as crucial to guide better practices. Final considerations: The approach allowed the recognition of contextual conditions for the implementation of the Evidence-Based Practice, which may coincide with similar scenarios, as well as increase the national scientific production on the subject, which is still scarce.